High‐Resolution Imaging of Human Cancer Proteins Using Microprocessor Materials. (14th July 2022) - Solares, Maria J.; Jonaid, G. M.; Luqiu, William Y.; Berry, Samantha; Khadela, Janki; Liang, Yanping; Evans, Madison C.; Pridham, Kevin J.; Dearnaley, William J.; Sheng, Zhi; Kelly, Deborah F.
Abstract: Mutations in tumor suppressor genes, such as Tumor Protein 53 (TP53), are heavily implicated in aggressive cancers giving rise to gain‐ and loss‐of‐function phenotypes. While individual domains of the p53 protein have been studied extensively, structural information for full‐length p53 remains incomplete. Functionalized microprocessor chips (microchips) with properties amenable to electron microscopy permitted us to visualize complete p53 assemblies for the first time. The new structures revealed p53 in an inactive dimeric state independent of DNA binding. Residues located at the protein‐protein interface corresponded with modification sites in cancer‐related hot spots. Changes in these regions may amplify the toxic effects of clinical mutations. Taken together, these results contribute advances in technology and imaging approaches to decode native protein models in different states of activation. Abstract : Microchip‐based substrates and high‐resolution imaging technology were used to resolve full‐length p53 structures from human cancer cells for the first time.